DNA Double-Strand Breaks Affect Chromosomal Rearrangements during Methotrexate-Mediated Gene Amplification in Chinese Hamster Ovary Cells - Jong Youn Baik; Hye-Jin Han; Kelvin H. Lee (MDPI AG, 2021)
Methotrexate (MTX)-mediated gene amplification has been widely used in Chinese hamster ovary (CHO) cells for the biomanufacturing of therapeutic proteins. Although many studies have reported chromosomal instability and extensive chromosomal rearrangements in MTX-mediated gene-amplified cells, which may be associated with cell line instability issues, the mechanisms of chromosomal rearrangement formation remain poorly understood. We tested the impact of DNA double-strand breaks (DSBs) on chromosomal rearrangements using bleomycin, a DSB-inducing reagent. Bleomycin-treated CHO-DUK cells, which are one of the host cell lines deficient in dihydrofolate reductase (Dhfr) activity, exhibited a substantial number of cells containing radial formations or non-radial formations with chromosomal rearrangements, suggesting that DSBs may be associated with chromosomal rearrangements. To confirm the causes of DSBs during gene amplification, we tested the effects of MTX treatment and the removal of nucleotide base precursors on DSB formation in Dhfr-deficient (i.e., CHO-DUK) and Dhfr-expressing (i.e., CHO-K1) cells. Immunocytochemistry demonstrated that MTX treatment did not induce DSBs per se, but a nucleotide shortage caused by the MTX-mediated inhibition of Dhfr activity resulted in DSBs. Our data suggest that a nucleotide shortage caused by MTX-mediated Dhfr inhibition in production cell lines is the primary cause of a marked increase in DSBs, resulting in extensive chromosomal rearrangements after gene amplification processes.